Speech Acts of The Main Character in Persuasion Movie Script Written by Ronald Bass and Alice Victoria Winslow - Bahar, Ismawaty; Moelier, Dahlia D.; Asyrafunnisa, Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2025)
This research aimed to find out the types of speech acts and the function of speech acts produced by the main character which contained in Persuasion movie script written by Ronald Bass and Alice Victoria Winslow. The writer used qualitative descriptive and pragmatic approach in analyzing the data. The data were obtained by reading, identifying, highlighting, and classifying the utterances that contained speech acts in the main character’s utterance based on Austin’s and Searle’s theories. The results found that there were 3 types of speech acts used in Persuasion movie script. Locutionary act which consisted of imperative, interrogative, and declarative. Illocutionary act which consisted of assertive, directive, commissive, expressive, and declarative. Then, perlocutionary act. Therefore speech acts had different functions according to their type, firstly, locutionary act had 3 functions, namely: imperative function, interrogative function, and declarative function. Illocutionary act had 5 functions, namely: assertive function, directive function, commissive function, expressive function, and declarative function. Then, perlocutionary acts only have one function. The locutionary speech act was the most dominant type of speech acts that appeared in Persuasion movie script.